AUTOPSY STUDY OF SUDDEN CARDIAC DEATH (Journal of Forensic Medicine & Toxicology, 2021)
Background:The causes of sudden cardiac death areundetected despite detailed postmortem examination,histological examination and toxicological analysisleading to negative autopsy in some cases. The presentstudy is carried out with a view to evaluate the victims ofsudden cardiac death (SCD) brought for medicolegalautopsy.Material and methods: The present cross sectional studyincluded 74 cases of sudden cardiac death within 24 hourswith history of chest pain or known ischaemic heartdisease brought for medicolegal autopsy. During theautopsy, heart and coronaries were dissected to find outany pathology and the subjected for histopathologicalexamination.Results: The victims of SCD were mostly males (85.1%)with peak incidence in older ages above 60 years (41.9%).Almost 84% of the victims had survival period of less than6 hours. Left anterior descending artery (64.9%) was thecommonest coronary artery involved with atherosclerosis.Most of the victims had double vessel block with 71.6%had coronary narrowing exceeding 75% stenosis. Therewas statistically significant positive correlation betweenthe coronary block and the age of the victim of suddencardiac death (p=0.007).Conclusion: Careful and detailed autopsy can beconducted in SCD to find out its cause.
Keywords: SCD; CAD; sudden cardiac death; MI